2015
DOI: 10.1002/micr.22414
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound visualization of the lymphatic vessels in the lower leg

Abstract: Ultrasonography can identify lymphatic vessels of the lower leg with precision and may aid lymphatic microsurgery for lymphedema. © 2015 Wiley Periodicals, Inc. Microsurgery 36:397-401, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 16 publications
(27 reference statements)
0
45
1
1
Order By: Relevance
“…The long‐term result of microsurgical treatment for lymphedema should be evaluated using imaging tests. Ultrasonography is inexpensive and painless; hence, it may be a useful choice for evaluating the transferred lymph nodes and lymphatic function in the future (Akita et al, ; Hayashi et al, ). Further studies investigating the correlation between findings in ultrasonography and lymphatic function are required.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term result of microsurgical treatment for lymphedema should be evaluated using imaging tests. Ultrasonography is inexpensive and painless; hence, it may be a useful choice for evaluating the transferred lymph nodes and lymphatic function in the future (Akita et al, ; Hayashi et al, ). Further studies investigating the correlation between findings in ultrasonography and lymphatic function are required.…”
Section: Discussionmentioning
confidence: 99%
“…For detection of lymphatic vessels in a region masked by dermal backflow pattern, or in patients with allergic reactions to ICG, we believe ultrasound, which is more common and simple, could substitute for ICG lymphography. Lymphatic vessels were reported to be illustrated as intermittent homogeneous, hypoechoic and specular misshapen images with ultrasonography in the lower leg of healthy volunteers . This research suggested the possibility of detecting lymphatic vessels under dermal backflow pattern of ICG lymphography in affected limb site of lymphedema, but no research has yet underlined the feasibility of ultrasound to detect the lymphatic vessels of lymphedema patients based on direct intraoperative observation during LVA.…”
Section: Introductionmentioning
confidence: 95%
“…The key element for a successful lymphedema surgery is to identify and locate functional LCVs before LVA is performed. Hayashi et al have utilized ultrasound to identify the location and depth of LCVs. Magnetic resonance lymphangiography was reported to find LCVs.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of lymphatico-venous anastomosis (LVA) in the 1960s, 1 it shed lights on surgical treatments for lymphedema. Supermicrosurgical LVA was first reported and popularized by Koshima et al [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] LVA can improve lymphedema by channeling lymphatic fluid from lymphatic collecting vessels (LCVs) into vein, thereby reducing accumulated lymph in the affected limb. However, pathological changes to LCVs can occur due to factors such as genetics, 21 aging, 22 soft tissue inflammation, 23 trauma, lymph node dissection, tumor resection, 21,24 and irradiation, 21,25 which can all lead to lymphedema.…”
Section: Introductionmentioning
confidence: 99%